Islamic Economic Principles: A Critical Review of Capitalism and a Vision for Justice - Muhammad Ifan Fadillah; Budi Supriatono Purnomo; Imas Purnamasari (Equity: Jurnal Ekonomi, 2024)
This article addresses the paradigmatic tension between capitalism and socialism in the quest for economic and social justice, with a specific focus on critiquing financial capitalism from an Islamic perspective. Using a literature review methodology, this study explores the theoretical foundations of these paradigms and highlights Islam’s distinct approach. The findings reveal that Islam critiques the financial theories underpinning capitalism, particularly its emphasis on the unrestricted pursuit of profit, accumulation of capital, and reliance on mechanisms like interest (riba) and speculative activities (gharar) that exacerbate economic inequality and social injustice. Islam does not align with the profit-driven individualism of capitalism or the state-centric control of socialism. Instead, it presents a transformative paradigm rooted in Islamic theology, advocating principles such as zakāt to ensure equitable wealth distribution, the prohibition of riba to prevent exploitative financial practices, and the prioritization of shared welfare over material accumulation. This paradigm, referred to as Transformative Islam, critiques the structural inequities of financial capitalism while emphasizing the moral imperative for justice, communal well-being, and sustainable economic systems. By integrating theological principles with practical methodologies, Transformative Islam offers a comprehensive and just alternative to exploitative financial systems.